Islam and the rearrangement of society–state relation in the reformation era of Indonesia - Yusdani, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article discusses the thoughts of Nurcholish Madjid and Abdurrahman Wahid regarding democratization in the reform era of Indonesia. It focuses on how Islam is articulated and implemented according to these two thinkers in the context of the changing of society-state relation in the reform era of Indonesia. To analyse and elaborate on their thoughts, the sociological and historical approaches as well as the prophetic sociology of knowledge are utilised or applied. It is argued here that the religio-political thoughts of the two thinkers go beyond a procedural democracy, arguing for a kind of democracy that is based on ethics and rationality where the relationship between strong society and the effective state in Indonesia is solidified and dignified.